Analysis of Students’ Mathematical Problem-Solving Ability on Whole Number Operations Based on Polya’s Framework - Baliani Putri Sopian, Salsabila; Turmudi, (International Conference on Elementary Education, 2025)
The research aims to determine the results of the analysis of students' abilities in solving problems in whole number calculation operations. This research is a qualitative descriptive study. The subjects in this study were 3 students with low, medium, and high mathematical problem-solving ability categories which were selected from a total of 31 students. Data collection techniques were carried out using written tests and interview. The research results obtained regarding students' mathematical problem-solving abilities are in low category with 77.4%, medium is 9.7%, and high is 12.9% ; (2) students with high abilities are very good at mastering all indicators of mathematical problem-solving abilities, but there are still errors in the indicators of understanding the problem; (3) students with moderate abilities have quite good abilities in understanding the problems presented in the questions, but are still lacking in other indicators; (4) students with low abilities are not able to understand the problem presented in the question well so that students have difficulty in carrying out the next problemsolving steps in the next indicators. Problem solving skills are still relatively low, so it is necessary to improve students' abilities in all indicators, especially in understanding problems.